A study of immunoglobulin M antibody to measles, canine distemper, and rinderpest viruses in sera of patients with subacute sclerosing panencephalitis. Issue 7 (July 1975) - Thomson, D; Connolly, J H; Underwood, B O; Brown, F
Abstract : Seven boys were studied who had the clinical features of subacute sclerosing panencephalitis (SSPE) and whose brain histology was consistent with SSPE. Measles antigen was detected in the seven brains by the direct fluorescent antibody method. Three out of the seven boys had in their sera measles specific immunoglobulin M (IgM) which was detected by the indirect fluorescent antibody method, and the cell receptors for it were acetone stable. A prozone effect was noted in the sera of two patients. The absorption of one patient's serum with Staphylococcus aureus to reduce the titre of immunoglobulin G (IgG) removed the prozone effect. Two of the boys who had high titres of measles specific IgM also had serum IgM which reacted with canine distemper virus antigen but the titres were eightfold lower. None of the boys had detectable rinderpest specific IgM in their sera.